Creative techniques for online learning assessment - Rambe, Sokhira LindaVinde (Universitas Islam Negeri Banda Aceh, 2021)
Online learning has been becoming a solution for schools, institutions, and universities that cannot run face-to-face learning. During the online learning process, there are challenges that stakeholders including teachers and lecturers often face. One of the challenges is in choosing assessment techniques which in this case is related to English learning assessment. Thus, the objective of this study is to elaborate some effective techniques for English learning assessment. Qualitative research was applied as a research design conducted at the English Education Department of the Institute for Islamic Studies of Padangsidimpuan. Ten lecturers of the English Department were chosen purposively as respondents and interview was used as a data collection technique. Then, data were analyzed through qualitative data analysis in which the data were described and elaborated in detailed ways. The findings revealed that there were many techniques that could be applied in English assessment methods. Among the methods are online tests using Google form application, discussion, and problem-solving, writing essays and summary, online presentation, multimedia presentation, mini-research, voice thread, storytelling, recording performance, online interview, and making content on social media. The study also unveiled that lecturers’ creativity is needed to create an objective and effective assessment for online learning.